Peptides in oncology. 1, Agonist and antagonist - Höffken, Klaus (Springer, 1992)
This volume provides an overview of the mechanisms of action and clinical efficacy of gonadotropin (luteinizing) hormone releasing (LH-RH) agonists and antagonists in hormone-sensitive neoplastic diseasis. It contains a detailed description of structural and functional aspects and presentsthe latest clinical results in treating benign and malignant neoplasias withLH-RH agonists as well as a detailed review of present knowledge of LH-RH antagonists.
Recent results in cancer research ; Vol. 124
Keywords: terapie hormonální - nádory - sborníky prací; rakovina - pokroky - sborníky prací; peptidy endogenní - onkologie - sborníky prací; endokrinologie; onkologie; alergologie a imunologie